2020
DOI: 10.1002/mgg3.1207
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of NGS panel and Sanger sequencing for genotyping CAG repeats in the AR gene

Abstract: Background The androgen receptor (AR) is a nuclear receptor, encoded by the AR gene on the X chromosome. Within the first exon of the AR gene, two short tandem repeats (STR), CAG and GGC, are a source of polymorphism in the population. Therefore, high‐throughput methods for screening AR, such as next‐generation sequencing (NGS), are sought after; however, data generated by NGS are limited by the availability of bioinformatics tools. Here, we evaluated the accuracy of the bioinformatics tool HipSTR in detecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…HipSTR accuracy was tested by comparing calls from 118 PCR WGS samples to capillary electrophoresis data, reporting about 98.8% consistency between the two datasets. Rocca et al [ 40 ] evaluated the accuracy of the bioinformatics tool HipSTR in detecting and quantifying CAG repeats within the androgen receptor gene of 228 infertile men. Their findings showed that the bioinformatics tool HipSTR is 100% accurate in detecting infertile men, and HipSTR was more accurate than Sanger in genotyping normal karyotype men.…”
Section: Discussionmentioning
confidence: 99%
“…HipSTR accuracy was tested by comparing calls from 118 PCR WGS samples to capillary electrophoresis data, reporting about 98.8% consistency between the two datasets. Rocca et al [ 40 ] evaluated the accuracy of the bioinformatics tool HipSTR in detecting and quantifying CAG repeats within the androgen receptor gene of 228 infertile men. Their findings showed that the bioinformatics tool HipSTR is 100% accurate in detecting infertile men, and HipSTR was more accurate than Sanger in genotyping normal karyotype men.…”
Section: Discussionmentioning
confidence: 99%
“…Although population studies based on a few loci frequently used microsatellite markers, which were once regarded as the standard genetic marker ( Jorde et al, 2000 ; Coates et al, 2009 ), until recently they were largely disregarded from large-scale analyses of genetic variation due to the challenges in their sequencing and genotyping ( Guilmatre et al, 2013 ; Mousavi et al, 2019 ). High quality PCR-free genomic sequencing as well as STR compatible mapping approaches surmounted the issue of low confidence, increasing the concordance with capillary data up to 98.5% ( Gymrek et al, 2012 ; Willems et al, 2017 ; Mousavi et al, 2020 ) and 100% with Sanger sequencing ( Rocca et al, 2020 ). With these advancements, it was shown that short tandem repeats correctly capture known population diversity patterns in humans ( Willems et al, 2014 ) and primate species ( Bilgin Sonay et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%